Degradation of roxarsone in a sulfate radical mediated oxidation process and formation of polynitrated by-products. Issue 85 (30th August 2016) - Ji, Yuefei; Shi, Yuanyuan; Kong, Deyang; Lu, Junhe
Abstract : Organoarsenicals such as roxarsone (ROX) are extensively utilized in the poultry industry, and land application of poultry litter is an important route by which arsenics are introduced into the environment. Abstract : Organoarsenicals such as roxarsone (ROX) are extensively utilized in the poultry industry, and land application of poultry litter is an important route by which arsenics are introduced into the environment. In the present study, degradation of ROX and structurally related nitrophenols by a heat activated persulfate (PS) oxidation process, one in situ chemical oxidation process (ISCO), was systematically explored. The effects of temperature, PS dosage, pH and natural water constituents ( i.e., fulvic acid, Cl − ) on the degradation of ROX were investigated. Products analysis by solid phase extraction (SPE) and liquid chromatography-electrospray ionization-triple quadrupole mass spectrometry (LC-ESI-MS/MS) revealed that 2, 4-dinitrophenol (2, 4-DNP) and 2, 4, 6-trinitrophenol (2, 4, 6-TNP) were generated as major intermediate products, suggesting denitration–renitration process occurred during SO4 ˙ − -based oxidation of ROX. Interestingly, the formation of polynitration by-products was further confirmed in heat activated persulfate oxidation of nitrophenols. Formation of inorganic arsenics during ROX degradation was measured by inductively coupled plasma-mass spectrometry (ICP-MS). It was evident that the arsenic substituent of ROX was converted to As(v ). On the basis of the intermediate products identified, detailed mechanisms and transformation pathways for ROX oxidation were proposed. Results manifest that heat activated PS oxidation could be an efficient approach to treat ROX contamination. However, post-treatment is necessary for complete removal of As(v ) to minimize ecotoxicological risks.